Risk factors for hospitalisation in Welsh infants with a congenital anomaly - Ho, P; Quigley, M; Tucker, D; Kurinczuk, J (BMJ Publishing Group, 2022)
Objectives To investigate risk factor associated with hospitalisation of infants with a congenital anomaly in Wales, UK.